Range extensions of three species of the family Caryophylliidae (Scleractinia) in the eastern Pacific Ocean - González-Romero, S.. H. Reyes-Bonilla & S.D. Cairns (Biodiversity Records, 2009)
The family Caryophylliidae Gray, 1847 (Cnidaria: Scleractinia), has almost 300 species in 42 genera (Cairns, Reference Cairns1999); these corals occur in all world oceans and at depths from less than 10 m to over 5000 m (Cairns, Reference Cairns2004). In this paper we report the finding of three species of this family from the southern California abyssal plain (off San Diego, California, USA) and in the Galápagos Islands, Ecuador, all of which represents new distribution records.